Growing the upper and lower parts of the plant - Baykulova Nasiba Abdunabiyevna (Genius Journals, 2022)
This article presents ideas about the art and methods of creating artificial forms of autumn trees and shrubs for gardeners and architects in the organization of landscape design
Keywords: garden; landscapes; art of topiary; Baroque